ANCA-Associated Vasculitis For the Allergist and Immunologist: A Clinical Update (Actualité en allergologie et en immunologie au Canada, 2023)
The anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are a group of multisystemic, relapsing, autoimmune diseases that include eosinophilic granulomatosis with polyangiitis (EGPA), granulomatosis with polyangiitis (GPA), and microscopic polyangiitis (MPA). While rare, with incidences between 1 and 25 per 100,000 individuals/year, these are diagnoses that should not be missed, as unrecognized, they are associated with significant morbidity and mortality. Despite their infrequency, international collaborative research has resulted in multiple new therapeutic strategies across all three diseases.